Methodology of Islamic economics: Typology of current practices, evaluation and way forward - Furqani, Hafas; Haneef, Mohamed Aslam (Bloomsbury Qatar Foundation Journals, 2015)
The sustainable development of Islamic economics as a discipline depends also on methodological development that provides a clear direction on how to appraise economic theories and provide evidence of its reliability. This paper attempts to study the methodology of Islamic economics in two ways: (1) by examining the works by scholars in their specific writings on this subject, and (2) by observing the writings on Islamic economics, banking and finance to see how Islamic economists develop their discipline. The paper found three categories of writings, namely: (1) the usul al-fiqh methodology applied in economics, (2) methodological pluralism that tries to utilize various methodologies developed in both western and Islamic tradition, and (3) conventional mainstream positive economic methodology applied in Islamic cases. These are evaluated thoroughly and suggestions are made as to what needs to be done to assist Islamic economics’ develop.